Measurement and correlation of the solubility of 3, 4-bis(3-nitrofurazan-4-yl)furoxan (DNTF) in different solvents. (October 2015) - Lan, Guan-Chao; Wang, Jian-Long; Chen, Li-Zhen; Hou, Huan; Li, Jing; Gao, Yu-Peng
Graphical abstract: Highlights: The laser monitoring system was used for measuring the solubilities of DNTF. Three correlation equations were adopted to correlate the experimental values. The three-dimensional figure between ln  x i and 1/ T, ln  T was obtained. Thermodynamic properties were calculated by the experimental solubilities. Abstract: A knowledge of the solubility of 3, 4-bis(3-nitrofurazan-4-yl)furoxan (DNTF) in different solvents is essential for crystallization and further theoretical studies. The laser monitoring system was used for measuring the solubility of DNTF in methanol, ethanol, acetic acid, benzene, toluene and n -butanol at temperatures ranging from (298.15 to 338.15) K. Polynomial empirical equation, ideal model and modified Apelblat equation were used to correlate the experimental values. The correlated results of three correlation equations present good consistency with the experimental values. In addition, the modified Apelblat equation produced higher accuracy than the polynomial empirical equation and the ideal equation. The standard dissolution enthalpy, standard dissolution entropy and the Gibbs energy were calculated from the experimental values. The solubility values of DNTF and correlation equations from this experiment would be invoked as basic data and models regarding the crystallization process of DNTF.